2018
DOI: 10.1016/j.ijrefrig.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal convective boiling of R1234yf, R134a, and R450A within a micro-fin tube

Abstract: This paper presents local convective boiling heat transfer and Fanning friction factor measurements in a micro-fin tube for R134a and two possible low global warming potential (GWP) refrigerant replacements for R134a, namely R1234yf and R450A. Test section heating was achieved with water in either counterflow or in parallel flow with the test refrigerant to provide for a range of heat fluxes for each thermodynamic quality. An existing correlation from the literature for single and multi-component mixtures was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Considering that Kedzierski and Kang (2018) provide a detailed description of the test apparatus and the measurement technique, it will be briefly described here. Figure 1 shows a sketch of the experimental apparatus that was used in all five NIST studies to establish and measure convective boiling heat transfer coefficients.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that Kedzierski and Kang (2018) provide a detailed description of the test apparatus and the measurement technique, it will be briefly described here. Figure 1 shows a sketch of the experimental apparatus that was used in all five NIST studies to establish and measure convective boiling heat transfer coefficients.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…NIST (2021) provides an online database that contains the complete corrected flow boiling heat transfer measurements of the Hamilton et al (2008), the Kedzierski and Park (2013), the Kedzierski and Kang (2016), and the Kedzierski and Kang (2018). The data presented in Domanski et al (2021) is also included in the database; however, it did not require correction.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was revealed that the heat transfer coefficients of R-134a and R-1234yf were similar. Kedzierski et al [9] studied the local convective heat transfer of R-1234yf and R-134a in microfin tubes with an inner diameter of 8.8 mm. The comparison results showed that the heat transfer performance of R-1234yf was 5% lower than that of R-134a.…”
Section: Introductionmentioning
confidence: 99%
“…Electric energy consumption with R450A was between 1.3% and 5.8% higher than that of R134a in a single-stage refrigeration system with a semi-hermetic compressor connected to a commercial vertical cabinet with doors placed inside a climatic chamber (Llopis et al, 2017). Additionally, Kedzierski and Kang (2018) studied the local convective boiling heat transfer in micro-fin tubes resulting, on an average, 15% lower for R450A in comparison with R134a.…”
mentioning
confidence: 99%